Comparative study on hazard identification and risk assessment in academic laboratory / Nur Athyratul Aqila, Nor Aimi Abdul Wahab and Maizatul Azra Mukhtar - Abdul Latif, Nur Athyratul Aqila; Abdul Wahab, Nor Aimi; Mukhtar, Maizatul Azra (2020)
Laboratory work, practical work as well as practical work-related experiment usually are carried out in a student-oriented laboratories. However, there are a broad wide of hazardous substance & equipment and no comprehensive review on hazard identification and risk assessment in academic laboratory. In this paper, a comparative study on hazard and risk assessment in academic laboratory was conducted to discuss on hazard and to address the various control measure to overcome or eliminate the hazard. A total of 64 publications on the hazard and risk assessment in academic laboratory were identified from Scopus, IEEE, Google Scholar, and manual searching. The study was guided by PRISMA and 9 selected journals were reviewed and integrated. From the comparison studies there are various types of hazard that can be found in academic laboratory such as chemical, physical, biological, electrical, and psychosocial. 44% discussed on specified hazard which is chemical and electrical and 56% discussed on nonspecified hazard. 43% used qualitative, 36% semi- qualitative and 21% quantitative method. Several recommendation such as provides a fixed standard system for hazard identification in academic laboratory and produce more experts in research paper is urged in order to improve and make progress for the future.